Online Buying and Selling on Shopee in the Perspective of Sharia Economic Law: An Analysis of Contracts and Transaction Principles - Tri Widia Wati (Saqifah: Jurnal Hukum Ekonomi Syariah, 2024)
Online buying and selling transactions through marketplace platforms such as Shopee have become a rapidly growing global phenomenon, including among the Indonesian Muslim community. This article aims to analyze the suitability of buying and selling transactions on Shopee with the principles of Sharia Economic Law, especially related to contracts and transaction principles. In the Sharia perspective, a transaction is considered valid if it meets the principles and conditions of the contract, namely the existence of the contracting party (seller and buyer), the object of the transaction, and clear ijab and qabul. This research uses a qualitative method with a normative-juridical approach, through the analysis of literature, fatwas, and regulations related to electronic transactions. The results of the study show that most transactions on Shopee are in accordance with the basic principles of contracts in Sharia Economic Law, such as the disclosure of information on goods and prices. However, there are several potential violations of sharia, especially related to the use of certain payment methods such as installments with interest and the risk of gharar (ambiguity) in product descriptions. Therefore, a deeper understanding of Islamic transactions is needed from Muslim users in order to be able to transact in accordance with Islamic values. This article provides recommendations for the development of more sharia-friendly marketplace features.